2023
DOI: 10.3389/fphys.2022.1078512
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise mobilizes CD8+ cytotoxic T cells and NK cells in lymphoma patients

Abstract: Background: Studies have shown that acute exercise can mobilize several leukocyte subpopulations in healthy individuals. Our aim was to investigate whether a 10-min acute exercise has an effect on immune cell proportions in lymphoma patients.Methods: This study included seven lymphoma patients referred to curative oncologic therapy. Three had Hodgkin and four non-Hodgkin lymphoma, one was female, and their mean age was 51. Patients underwent a 10-min acute exercise on a bicycle ergometer at moderate exercise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In our previous studies, we have observed an association between BMI and leukocyte count, but surprisingly not in this study. In a study with lymphoma patients in same settings we found that BMI correlated positively with change in NK cell count and granulocyte proportion between rest and exercise and with baseline levels of CD14 + CD16 + and CD14 − CD16 + monocytes 34 . Moreover, high BMI is associated with higher leukocyte count in otherwise apparently healthy people with various degrees of overweight and obesity 35 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our previous studies, we have observed an association between BMI and leukocyte count, but surprisingly not in this study. In a study with lymphoma patients in same settings we found that BMI correlated positively with change in NK cell count and granulocyte proportion between rest and exercise and with baseline levels of CD14 + CD16 + and CD14 − CD16 + monocytes 34 . Moreover, high BMI is associated with higher leukocyte count in otherwise apparently healthy people with various degrees of overweight and obesity 35 .…”
Section: Discussionmentioning
confidence: 72%
“…After centrifugation, the cells were resuspended in 300 µL of PBS and samples were pipetted into a flat bottom 96-well plate. As applied previously 34 , 48 52 , samples were analyzed by running 150 µL of each sample with a BD LSR Fortessa™ flow cytometer (BD Biosciences, San Jose, USA) on the same day using BD FACSDiVa v.8 program (BD Biosciences, San Jose, USA). All samples were analyzed by the same person under the same conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In healthy individuals, the number of circulating neutrophils, lymphocytes, and monocytes increase in response to different types of exercise (15)(16)(17)(18). Previously, we showed that acute 10-minute light-to-moderate-intensity exercise increases the number of total leukocytes, CD8 + T cells, CD19 + B cells, CD16 + NK cells, and CD14 + CD16 + monocytes in the circulation of newly diagnosed breast cancer patients (13) and fairly similar responses were seen in lymphoma patients (19). These studies, however, did not include pro-tumorigenic cells, for example MDSCs or regulatory T cells.…”
Section: Introductionmentioning
confidence: 92%
“…Lactate concentration (Lactate Scout 4, EKF Diagnostics, Barleben, Germany), blood pressure (Apteq AE701f, Rossmax Swiss GmbH, Berneck, Switzerland), and heart rate (Palmsat 2500, Nonin, Plymouth, USA) were measured at the same time points as the blood samples were drawn, and heart rate was also measured continuously during the exercise with Polar H10 heart rate sensor (Polar Electro Oy, Kempele, Finland). Participants' rating of perceived exertion (RPE) was determined with a Borg scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Rate pressure product (RPP) was measured by multiplying systolic blood pressure by heart rate.…”
Section: Participantsmentioning
confidence: 99%
“…Cytotoxic T cells and natural killer (NK) cells are important for defense against tumor cells, and these cells seem to be activated during exercise [33,34]. In particular, CD8+ T cells and NK cells, rather than CD4+ T cells, are significantly effective during acute exercise [35], suggesting that different exercise intensities specifically affect the immune response differently [36].…”
Section: Effects Of Physical Activity On Pancreatic Cancer Via Obesit...mentioning
confidence: 99%